Association between polymorphisms in genes encoding estrogen receptors (ESR1 and ESR2) and excreted bisphenol A levels after orthodontic bracket bonding: a preliminary study - Karla C. Horta; Guido A. Marañón-Vásquez; Mírian A. N. Matsumoto; Marília R. Moreira; Fábio L. Romano; Alberto Consolaro; Israel D. de Souza; Tamires A. V. Brigante; Maria E. C. Queiroz; Paulo Nelson-Filho; Erika C. Küchler (SpringerOpen, 2018)
Abstract Background Bisphenol A (BPA) is released from orthodontic composites used for bracket bonding. Genetic variations could modify the metabolism of this chemical within the organism. Considering that free BPA binds to estrogen receptors causing harmful effects to health, the present in vivo study aimed to evaluate the association between genetic polymorphisms in genes encoding estrogen receptors (ESR1 and ESR2) and excreted BPA levels in orthodontic patients. Methods Quantification of BPA levels in the urine of 16 patients was performed in a gas chromatograph mass spectrometer before (T0), at 24 h (T1), and 1 week (T2) after bracket bonding. DNA was extracted from saliva, and one genetic polymorphism in ESR1 (rs2234693) and two in ESR2 (rs4986938 and rs1256049) were analyzed by real-time PCR. Increases in BPA levels in the urine at T1 and T2 were grouped according to the genotype, and mean differences were compared by unpaired T test or Mann-Whitney test according to the normality of the data. The established alpha was 5%. Results BPA levels increased significantly at T1 and T2. There were no statistically significant differences in the increases in BPA levels according to the genotype for any genetic polymorphism (P > 0.05), at neither 24 h nor 1 week after bracket bonding. Conclusions The results suggested that there are no association between excreted BPA levels after bracket bonding and the evaluated genetic polymorphisms in ESR1 and ESR2. Further research should be performed in order to confirm these results.